(untitled) (Research, Society and Development, 2023)
With the growing demand for mechanical services across the world, the importance of proper education and training for mechanics has become increasingly evident. However, many companies in the field still face difficulties in hiring qualified professionals and are not always able to provide quality training due to lack of time and resources. Through a case study this work aims to highlight the benefits of using an EAD platform, fed with videos and images and documents of maintenance performed on mechanical equipment in order to improve the quality of learning of the company’s newly hired workforce, enhancing the medium and long term production results. The study presents the implementation of a platform to qualify the former employee. With this, it is noted that this method is an efficient way to enhance the training of mechanics, since they would have access at a distance, to a database with important information about the work that would be carried out by them later, allowing the professional to know the obstacles in maintenance, reducing the rate of errors in the process, aiming at saving time and increasing production..